Stimulus intensity modulates multisensory temporal processing - Krueger Fister, Juliane; Stevenson, Ryan A.; Nidiffer, Aaron R.; Barnett, Zachary P.; Wallace, Mark T. (Neuropsychologia, 2016)
One of the more challenging feats that multisensory systems must perform is to determine which sensory signals originate from the same external event, and thus should be integrated or “bound” into a singular perceptual object or event, and which signals should be segregated. Two important stimulus properties impacting this process are the timing and effectiveness of the paired stimuli. It has been well established that the more temporally aligned two stimuli are, the greater the degree to which they influence one another’s processing. In addition, the less effective the individual unisensory stimuli are in eliciting a response, the greater the benefit when they are combined. However, the interaction between stimulus timing and stimulus effectiveness in driving multisensory-mediated behaviors has never been explored – which was the purpose of the current study. Participants were presented with either high- or low-intensity audiovisual stimuli in which stimulus onset asynchronies (SOAs) were parametrically varied, and were asked to report on the perceived synchrony/asynchrony of the paired stimuli. Our results revealed an interaction between the temporal relationship (SOA) and intensity of the stimuli. Specifically, individuals were more tolerant of larger temporal offsets (i.e., more likely to call them synchronous) when the paired stimuli were less effective. This interaction was also seen in response time (RT) distributions. Behavioral gains in RTs were seen with synchronous relative to asynchronous presentations, but this effect was more pronounced with high-intensity stimuli. These data suggest that stimulus effectiveness plays an underappreciated role in the perception of the timing of multisensory events, and reinforces the interdependency of the principles of multisensory integration in determining behavior and shaping perception. •We tested the interaction between timing and effectiveness of audiovisual stimuli.•Subjects judged audiovisual simultaneity with varying stimulus onset asynchronies (SOAs) and stimulus saliencies.•Perceived simultaneity decreases with SOA for both stimulus intensities.•The rate of perceived simultaneity decreases quicker for high-saliency conditions than for low-saliency conditions.•The tolerance of larger temporal offsets increases with decreasing stimulus effectiveness.•Our findings suggest an interdependence between stimulus factors during multisensory integration.•This interdependence can shape perception and behavior.